The relationship between audit committees, external auditors, and internal control systems: a literature review and a research agenda - Wehrhahn, Christoph; Velte, Patrick (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This paper aims to focus on the relationship between audit committees, external auditors and internal control systems (ICS) and strives to point out mutual influences between the instances to provide an integrated perspective for firms’ multilateral monitoring mechanisms. Furthermore, this study emphasizes the incorporation of sustainability and fraud considerations into the traditional roles of audit committees and auditors.
Keywords: Internal Control System; Internal Audit Function; Audit Committee; External Auditor; Corporate Governance